Enhancing Community Skills as an Effort to Strengthen Family Resilience - Mutmainah, Nur Fitri; Saharuddin, Erni; Warastri, Annisa; Utsany, Royan (Universitas Muhammadiyah Surakarta, 2024)
Padukuhan Karangtengah, Gamping, Sleman has a community condition with a divorce rate reaching 27%, juvenile delinquency 17% of the village youth, and community health conditions that are starting to decline as shown by the coverage of under-five malnutrition at 67%. The condition of family vulnerability has an impact on various aspects ranging from social, psychological, economic and health conditions. Realizing the importance of strengthening family resilience, it is necessary for families to create strong family resilience. Family resilience will greatly impact various aspects of life. The service method is carried out using Participatory Rural Appraisal and Participatory Learning and Action (PLA). The targets of this activity are married couples with a marriage age of <5 years, and PKK members. The activities carried out are strengthening the resilience of mosque-based families and initiating the formation and strengthening of the Women's Farmer Group (KWT). From these activities, it was obtained that community understanding regarding the concept of family resilience increased, community knowledge regarding institutions increased and a KWT was formed which in the future will carry out activities for family food security.